Solving chemical problems for students of the College of Education for Pure Sciences - Ibn Al-Haythem - Jasim, Alyaa AbdulAmeer; Ahmed, Basma Mohamed (Al-Adab Journal, 2023)
The aim of the research is to know the significance of the difference between the students of the research sample on the test of solving chemical problems as a whole and on each of its fields. The research sample consisted of (200) students from the fourth stage of the University of Baghdad, College of Education for Pure Sciences / Ibn Al-Haythem / Department of Chemistry In the morning and evening studies, i.e. (50%) of the research community, the research tool was a chemical problem solving test of (25) paragraphs with six areas by adopting the Hayes classification to solve problems represented by (defining the problem, representing the problem, choosing the solution plan, clarifying the solution plan , conclusion and (verification & evaluation). The results of the research showed that there is a statistically significant difference between the students of the research sample in the test of solving scientific problems as a whole to an acceptable degree, and the results showed a statistically significant difference in each of the areas of chemical problem solving between The students of the research sample for the areas (defining the problem, representing the problem, choosing a solution plan, clarifying the solution plan, conclusion) to an acceptable degree, but the field of verification and evaluation was not statistically significant, and the research recommended the need for education faculties to pay attention to solving chemical problems It covers all its fields and incorporates it into the theoretical and practical courses.